Should a laparoscopic repair be the first choice in incarcerated inguinal hernia - Akay, Tamer; Akici, Murat (International Surgery Journal, 2020)
Background: An important part of the procedures for admission to emergency surgery is incarcerated inguinal hernia repair. Minimally invasive surgical procedures have led surgeons to perform these operations laparoscopically. The aim of this study was to demonstrate the safety of laparoscopic inguinal hernia repair in patients admitted to the emergency department with incarcerated inguinal hernia. Methods: The files of patients who underwent laparoscopic surgery for incarcerated inguinal hernia between January 2015 and June 2019 in Bandirma State Hospital General Surgery Clinic was retrospectively reviewed. Pearson Chi-Square test was used as statistical method. Version 18 of the SPSS program was used. P<0.05 was considered significant as it should be. Results: A total of 63 patients were included in the study. The mean age was 52.8 years. A total of 64 repairs were performed on the right side in 41 (65%) cases, on the left side in 21 (33.3%) cases and on both sides in one (1.58%) case. Four (6.25%) of 63 patients had strangulation. Three of these patients (4.68%) had strangulated hernia, and one (1.56%) had strangulated and incarcerated hernia. Four patients (6.25%) presented with ileus. The mean operation time was 65 minutes (35-110 minutes). Mean duration of hospitalization was 2.4 days. The rate of minor complications was 4.68%. Only one (1.56%) major complication was iatrogenic small intestinal perforation. The mean follow-up time was 25.2 months. There was no early recurrence in patients. Conclusions: We suggest that laparoscopic transabdominal preperitoneal hernia repair can be performed safely in emergency procedures in patients with incarcerated inguinal hernia.